Identification and Evaluation of Potential Land Resources to Support the Development of Agricultural Commodities for Food Crops Zone - Nurdiyanto Agung Prasetya; . Hikmatullah; . Asisah; Muhamad Buce Saleh; Suria Darma Tarigan (UNIVERSITY OF LAMPUNG, 2014)
To support the goverment purpose to reach the food security, a land use study is needed. The aim of the research was to provide an information of characteristics of land resources through the identification and evaluation of potential landresources and that suitable for food crops in Mamuju District South Sulawesi. The research method used landscape approach to mapping land units as the basis for preparing the soil map unit/DEM compared with field data survey. A case study was done in Mamuju District, West Sulawesi the results showed that the land in Mamuju for paddy covering was suitable enough of 115,250 ha and 54,883 ha of marginal fit, while for dryland crops were 106 978 ha was quite suitable and appropriate marginal was 82,592 ha. However, for cocoa fit enough land was 153,397 ha and corresponding marginal was 485,743 ha. Biophysical constraints were the erosion of land use/steep slopes, drainage, seasonal flooding, toxicity and nutrient retention. Direction of land use for agriculture in Mamuju for Rice crop area was 49,345 ha (6.23%), food crops rice and dry land was 10,680 ha (1.35%), dryland crops/crops was 101,785 ha (12.85%), perennial/Cocoa was 90,488 ha (11.42%), and conservation land was 532,245 ha (67.18%).Keywords : Cland crops, land identification, soil evaluation [How to Cite: Nurdiyanto AP, Hikmatullah, Asisah, MB Saleh, and SD Tarigan. 2014. Identification and Evaluation of Potential Land Resources to Support the Development of Agricultural Commodities for Food Crops Zone. J Trop Soils 19: 53-61. Doi: 10.5400/jts.2014.19.1.53]